Avaliação do estado nutricional e fatores associados em idosos na cidade de Veranópolis - De Lucca, Eduarda Willers (2020)
The main objective of this research was to assess the nutritional status of the elderly in the city of Veranópolis/RS. The specific objectives were to investigate the factors associated with nutritional risk, to analyze the variables that have the highest Chance Ratio of the elderly presenting nutritional risk, to diagnose the nutritional risk index and the malnutrition index of the elderly surveyed. This was a cross-sectional, home-based observational study, which targeted individuals aged 60 years or over, in households, in the urban and rural areas of that location. The data were collected through the application of a structured questionnaire, investigating the socioeconomic status, demographic data, marital status, oral hygiene habits, behavior and general health history and a nutritional assessment was made. They were also conducted to oral clinical examinations, to check tooth loss, use and the need to use prostheses. For statistical analysis, the program SPSS (Statistical Package for the Social Sciences) was used. Associations between dependent and independent variables were assessed using the chisquare or Fisher's exact tests, presented through the frequency distribution. The results obtained were the prevalence of nutritional risk of 14.5% (N = 41) and malnutrition ≤ 0.36% (N = 1). In the univariate analysis, the variables with the highest Odds Ratio (OR) of the elderly presenting nutritional risk were age, retirement, marital status, the number of self-reported diseases, daily use of 6 or more medications, access to the dentist in the last 12 months and edentulism. In the final multivariate analysis of the association between nutritional risk and exploratory variables, users of 6 or more daily medications and edentulous elderly remained associated with nutritional risk. The conclusion was that the prevailing nutritional risk index can be considered low, when compared with the other studies cited, which varied between 25% and 50.2%, except for one, which was 10%. The malnutrition rate can also be considered low, as only one elderly person was considered malnourished, since the studies referred to values from 3.4% to 46.4%, with the exception of one, which found no case. However, the association between nutritional risk, the constant use of medications and edentulism verified in the study, indicate the need for measures to be taken to solve these problems, seeking to eliminate risks, improve the nutritional status of the elderly and prevention of diseases resulting from or related to poor diet.